الاساليب النبوية في إدارة الحياة الزوجية - بوقطة, ميلود; رزيق, عبد النور (University of Eloued-جامعة الوادي, 2022)
تناولت الدراسة الأساليب النبوية في إدارة الحياة الزوجية حيث طرحت إشكالية كيف ساهمت الأساليب النبوية في إدارة الحياة بفاعلية ونجاعة؟ وللإجابة عليها قسمت من خلال الخطة إلى مبحثين، حيث تناول المبحث الأول الإطار المفاهيمي للأساليب النبوية في إدارة الحياة الزوجية من خلال ثلاثة مطالب: مفهوم الأساليب النبوية في اللغة والاصطلاح في مطلب أول، ومفهوم إدارة الحياة الزوجية كمركب إضافي في مطلب ثان، وإدارة لحياة الزوجية بين اكتساب الحقوق والقيام بالواجبات في مطلب ثالث، وأما المبحث الثاني فقد عالج الاطار التطبيقي للأساليب النبوية في إدارة الحياة الزوجية من خلال التطبيقات النبوية لأسلوب الحكمة والحوار والمشاركة الوجدانية في الحياة الزوجية في مطلب أول ، فبينت فيه أسلوب المجالسات والمؤانسات وأسلوب القيام بحقوق المعاشرة الزوجية، وكذا أسلوب حفظ العهد والوفاء وأسلوب مراعاة المشاعر الزوجية، وأما المطلب الثاني فقد تطرق للحلول النبوية للمشكلات الزوجية كحادثة الإفك، والمطالبة في الزيادة بالنفقة ومشكلة حادثة العسل وقصة القصعة، وخلصت الدراسة إلى نتائج واقتراحات أهمها أن الأساليب النبوية بقسميها العادية والاستثنائية قد لعبت دورا محوريا في إدارة الحياة الزوجية بفعالية ونجاعة، وأنه ينبغي على الأزواج معرفة الحقوق والواجبات والتدرب على مهارات إدارة الحياة الزوجية من خلال التعمق في دراسة الهدي النبوي.. The study dealt with the prophetic methods in managing married life, as it raised the problem of how did the prophetic methods contribute to the effective and efficient management of life? In order to answer it, it was divided through the plan into two sections, where the first topic dealt with the conceptual framework of the prophetic methods in managing married life through three demands: the concept of prophetic methods in language and terminology in a first requirement, and the concept of managing married life as an additional compound in a second requirement, and management of married life Between the acquisition of rights and the fulfillment of duties in a third requirement. As for the second topic, it dealt with applied models of the prophetic transactions in married life through the daily dealings in the prophetic married life in a first requirement, in which the councils, sympathies and carrying out the rights of marital cohabitation, as well as keeping the covenant and fulfillment and taking into account marital feelings. As for the second requirement, it touched on practical prophetic models in solving marital problems, such as the incident of defamation, the demand for an increase in alimony, the problem of the honey incident and the story of the bowl. And that spouses should know the rights and duties and train in the skills of managing marital life by deepening the study of guidance Prophetic.
مذكرة ماستر
Keywords: إدارة الحياة الزوجية، الأساليب النبوية; marital life management, prophetic methods, daily dealings, effectiveness.